Kamarimusiikkikonsertti: Tšaikovsky, Prokofjev - Anttila, Tanja; Anttila, Kaisa (2004)
Abstract: Chamber music concert.
Keywords: Tšaikovski, Pjotr; Prokofjev, Sergei; duot; konsertit; kamarimusiikki; viulu; piano